2011
DOI: 10.1111/j.1748-7692.2010.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Life history of the Indo‐Pacific humpback dolphin in the Pearl River Estuary, southern China

Abstract: We studied life history characteristics of the Hong Kong/Pearl River Estuary population of Indo‐Pacific humpback dolphins (Sousa chinensis), based on data from 120 specimens stranded between 1995 and 2009, 40 individuals biopsied at sea, and a long‐term (14+ yr) photo‐identification study. Ages were determined for 112 specimens by thin‐sectioning teeth and counting growth layer groups. Estimated length at birth was 101 cm. Longevity was at least 38 yr, and there was little difference in growth patterns of male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 20 publications
(23 reference statements)
4
97
0
1
Order By: Relevance
“…This subspecies has complex pigmentation with dramatic developmental changes (see Jefferson et al 2012;Jefferson and Rosenbaum 2014). It is medium to dark grey at birth and then transitions with age through various degrees of light and dark spotting while the base layer colour also changes from being primarily grey to white.…”
Section: Diagnosismentioning
confidence: 99%
“…This subspecies has complex pigmentation with dramatic developmental changes (see Jefferson et al 2012;Jefferson and Rosenbaum 2014). It is medium to dark grey at birth and then transitions with age through various degrees of light and dark spotting while the base layer colour also changes from being primarily grey to white.…”
Section: Diagnosismentioning
confidence: 99%
“…Analysis of the teeth, particularly the wear on them, and the skin colour based on the life history information of the Indo-Pacific humpback dolphin (Jefferson et al, 2012) suggested that the dolphin was around 40years old at the time of the study. A hearing test has been deemed an important part of the health assessment of stranded dolphins.…”
Section: Subjectmentioning
confidence: 99%
“…There is very little information on contaminant levels in ETS Sousa, but high levels of persistent organic pollutants in PRE Sousa are considered as risks to their health (Minh et al 1999, Parsons 2004, Leung et al 2005, Jefferson et al 2006. High rates of neonatal mortality in the PRE Sousa may be caused by exposure of breeding females to environmental contaminants (Jefferson et al 2012). …”
Section: Pollution In the Fisheries Sectormentioning
confidence: 99%
“…Matrilineal social structure has not been conclusively demonstrated for humpback dolphins, but post-reproductive female longevity (a hallmark of matrilineal societies; McAuliffe & Whitehead 2005) is suspected in both the PRE (Jefferson et al 2012) and ETS populations (Dungan 2011). Breeding females appear to have important social network positions in ETS Sousa.…”
Section: General Behavioural Consequences Arising From Individual Deathsmentioning
confidence: 99%